ORIGINS OF CULTURAL VALUESUKRAINE - Ременець, О. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2014)
The article analyzes the Ukrainian cultural values, which are based on archetypes of culture.